Bullying in an Aboriginal Context - Coffin, Juli; Larson, Ann; Cross, Donna (The Australian Journal of Indigenous Education, 2010)
Abstract Aboriginal children appear to be more likely to be involved in bullying than non-Aboriginal children. This paper describes part of the “Solid Kids Solid Schools” research process and discusses some of the results from this three year study involving over 260 Aboriginal children, youth, elders, teachers and Aboriginal Indigenous Education Officers (AIEO's), and an Aboriginal led and developed Steering Committee. It is the first study that contextualises Aboriginal bullying, using a socio-ecological model where the individual, family, community and society are all interrelated and influence the characteristics and outcomes of bullying. This paper demonstrates that for Aboriginal children and youth in one region of Western Australia, bullying occurs frequently and is perpetuated by family and community violence, parental responses to bullying and institutional racism. Addressing bullying requires actions to reduce violence, foster positive cultural identity and reduce socio-economic disadvantage.